PENERAPAN GOOD CORPORATE GOVERNANCE PADA BANK SYARIAH INDONESIA (BSI) KCP TEBING TINGGI - Niswa Auliya Lubis; Siti Nurhalimah; Tasya Nadilla; Ahmad Wahyudi Zein (CV. Barokah Publsiher, 2025)
This research aims to analyze the implementation of Good Corporate Governance (GCG) at Bank Syariah Indonesia (BSI) Tebing Tinggi Sub-Branch Office. The study focuses on five key principles of GCG, namely transparency, accountability, responsibility, independency, and fairness. A descriptive qualitative approach was applied, using interviews, observations, and document studies as data collection techniques. The findings reveal that GCG implementation at BSI Tebing Tinggi is generally well-executed, supported by management commitment and an Islamic work culture. However, transparency and internal monitoring still need improvement. The study recommends strengthening digital-based reporting systems and enhancing human resource competencies to optimize GCG practices in branch-level Islamic banking operations.